The Effectiveness of Digital Attraction and Promotion on the Decision to Visit the Beach Tourism Area of Jember Regency with Interest in Visiting as an Intervening Variable - Navalina, Anita Eka; Nursa'id, Nursa'id; Herlambang, Toni; Sanosra, Abadi (International Journal of Management Science and Information Technology, 2024)
The aim of this research is to determine and analyze directly and indirectly the influence of the effectiveness of digital attractions and promotions on visiting decisions through visiting interest as an intervening variable in the coastal tourist area of Jember Regency. The sample size for this research was 400 respondents. The analysis technique used is Structural Equation Model (SEM) using WarpPLS 7.0. The results of data analysis show that the variable Effectiveness of attractions has a significant influence on interest in visiting, digital promotion has a significant influence on interest in visiting, Effectiveness of attractions has a significant influence on the decision to visit, digital promotion has a significant influence on the decision to visit, interest in visiting has a significant influence on the decision to visit. Indirectly, the effectiveness of digital attractions and promotions has a significant effect on visiting decisions through visiting interest as an intervening variable. The results of data analysis show that the variables of effectiveness of attraction, interest in visiting and digital promotion partially have a significant influence on the decision to visit the coastal tourist area of Jember Regency.